A Long Walk to Purgatory The Tales of Dante & Mashudu - Martalas, Chariklia (UJ Press, 2023)
A Long Walk to Purgatory is a play that places Dante in the South African context. It works with the idea that dead poets must guide living poets through the afterlife on a journey of poetic reckoning. It is now Dante's turn to guide a poet, as he was once guided by Virgil. Dante comes to meet Mashudu, a South African poet in her Dark Wood. He comes to take her through Inferno and Purgatory where she meets South African characters along the way including Jan Van Riebeeck and John Dube. Driving the play is the notion that poets need to know where they come from in order to play their role as aids to how a nation understands itself. This means Mashudu has to witness the truth of her context both in terms of the narrative of South Africa as a country and her own personal morality. Mashudu, guided by Dante, reckons with her understanding of South Africa's past such as with witnessing the punishment of Verwoerd, to reckoning with the country's present including a domestic abuser. Mashudu is also faced with the precariousness of her own morality when she meets an old friend in Purgatory. As the play continues, Dante becomes Mashudu's friend showing that friendship can cross centuries and contexts for poets share their role as poets no matter the society they belong to. Both Mashudu and Dante are connected by their unwavering commitment to their own moral imagination. Virgil as comic relief completes the picture as narrator, cementing the idea that the poets of the past are deeply connected to the poets of the present. Ultimately A Long Walk to Purgatory aims to show the importance of literature to both be grounded in and transcend particularities of time and place. Literature can ultimately open up a new space for us that is both informed by a context but is intrinsically connected to a wider humanity.